Urban geology process-oriented concepts for adaptive and integrated resource management - Huggenberger, Peter; Epting, Jannis (Springer Basel, 2011)
Urban subsurface resources and particularly urban groundwater are vulnerable to environmental impacts, and their rational management is of major importance. In this book a multidisciplinary team of specialists and scientists presents innovative process-oriented approaches to the sustainable use of these resources. The included case studies from northwestern Switzerland describe representative environments and are relevant for urban areas in general. They illustrate the protection of groundwater; river restoration; engineering and hydrogeological questions related to urban infrastructure and management concepts; as well as monitoring, modeling and remediation strategies for contaminated sites; problems caused by karst in urban environments; the use of shallow geothermal energy; and natural hazards such as flood events and earthquakes. It is demonstrated that modern quantitative earth sciences can contribute significantly in finding solutions concerning the sustainable use of subsurface resources in urban environments. The book is an invaluable source of information for hydrogeologists, geologists, urban planners, water supply engineers, and environmental agencies.